Effects of Payena dasyphylla (Miq.) on Hyaluronidase Enzyme Activity and Metalloproteinases Protein Expressions in Interleukin-1β Stimulated Human Chondrocytes Cells - Kamini, Citalingam; Seema, Zareen; Khozirah, Shaari; Syahida, Ahmad (BioMed Central Ltd., 2013)
Hyaluronidases have been found as the target enzymes in the development of osteoarthritis (OA) disease. While there is still no curative treatment for this disease, recent studies on the treatment of OA were focused on the effectiveness of natural products which are expected to improve the symptoms with minimal side effects. The aim of this study was to screen selected Malaysian plants on their anti-hyaluronidase activity as well as to evaluate the active plant and its derived fractions on its potential anti-arthritic and antioxidant activities.